KEMAMPUAN ASIMETRI INFORMASI, KETIDAKPASTIAN LINGKUNGAN, BUDGET EMPHASIS, DAN KAPASITAS INDIVIDU SEBAGAI VARIABEL MODERASI TERHADAP PARTISIPASI ANGGARAN PADA BUDGETARY SLACK - Asak, P. Rani Adnyani; Yasa, Gerianta Wirawan; Putra Astika, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Public sector budget is the instrument of accountability to the management of public funds and the implementation of programs, which were funded by public. This budgeting system is also known as budget based on performance. Budgeting system based on performance is an efficient and participatory development process with the hope that it can improve agent performances. Government as an agent proposes further budget gets legalistas of the legislative. The growth of local budget in Badung Regency, Bali from 2006 until 2013 indicated that there was a budgetary slack . This happened because there were a few contingent factors that could strengthen or weaken the effect of correlation budgetary participations with the budgetary slack . This research will examine the ability of information asymmetry, environmental uncertainty, budget emphasis and individual capacity as moderating variables for budgetary participations on a budgetary slack . All data were collected using a survey method with multiple questioners and were analyzed using moderated regression analysis method. Environmental uncertainty is the only variable which can moderate (weaken) the impact of budgetary participation on the budgetary slack from a series of moderating variables which were included in the analysis of this study.
Keywords: Budgetary Participation, Information Asymetr, Environmental Uncertainty, Budget Emphasis, Individual Capacity, Budgetary slack.